Risk Factors for Clonorchis sinensis Infection in Residents of Binyang, Guangxi: A Cross-Sectional and Logistic Analysis Study - Xu, Meng; Jiang, Yanyan; Yin, Jianhai; Cao, Shengkui; Shen, Yujuan; Cao, Jianping (Frontiers in Public Health, 2021)
Background: Clonorchiasis is a serious food-borne parasitic disease caused by Clonorchis sinensis infection. C. sinensis, a major fish-borne trematode, is a known causative agent of cholangiocarcinoma. The risk factors for C. sinensis infection include individual eating behaviors and environmental factors. In this study, we evaluated the C. sinensis infection rate and the associated risk factors among residents in Binyang County, Guangxi, China. Methods: In 2016 and 2017, five villages from Binyang, Guangxi were selected by multistage cluster random sampling for a cross-sectional study. A modified Kato-Katz thick smear method was used to examine C. sinensis eggs in fecal samples in triplicate (three smears for each sample). Both uni-variate and multi-variate logistic regression analyses were carried out to identify the risk factors for C. sinensis infection. Results: A total of 1,977 fecal samples were collected from villagers in the investigated areas. The overall infection rates of C. sinensis in Binyang County was 20.49% (405/1,977). The mean age of participants was 39.42 ± 23.48 (range: 3–89 years old), and the highest infection rate (33.72%) was seen in the age group of 40-49 years old, followed by those aged 50–59 (31.83%). Multi-variate logistic regression analysis showed that higher infection rates were significantly associated with males (aOR = 6.51, 95% CI = 4.67–9.08), Zhuang (aOR = 2.41, 95% CI = 1.62–3.59), ages (aOR = 33.51, 95% CI = 10.13–110.86), frequency of raw fresh fish consumption (aOR = 14.56, 95% CI = 9.80–21.63), and close contact with cats and dogs (aOR = 1.53, 95% CI = 1.02–2.30). Occupations and education levels showed no significant association with C. sinensis infection (P > 0.05). Conclusions: High levels of C. sinensis infection were observed among residents in Binyang County, Guangxi. Intervention strategies should be strengthened among the investigated population at high risk, such as males, Zhuang and older individuals, especially those who frequently eat raw fresh fish. In addition, the individuals contacting with cats and/or dogs were observed to have significantly higher infection rate of C. sinensis than those having no contact with cats and dogs. The association between contacting with cats and/or dogs and C. sinensis infection needs to be explored and confirmed in the future study by more epidemiological investigations of human C. sinensis infection from different areas.